Glycosylation of CD44 negatively regulates its recognition of hyaluronan (The Rockefeller University Press, 1995)
Although CD44 is expressed on a wide variety of cell types, few of them use it to recognize the ligand hyaluronan (HA). A glycosylation- defective clone of Chinese hamster ovary cells (Lec 8) bound HA, demonstrating that complete processing of glycoproteins with addition of a full complement of sialic acid is not required. On the contrary, subsequent findings revealed that complex sugars on CD44 can actually inhibit ligand recognition. Two subclones of wild-type Chinese hamster ovary cells with similar amounts of surface CD44 were isolated on the basis of HA binding and found to differ with respect to CD44 size as well as staining with fluorescent lectins. Treatment of the nonbinding clone with tunicamycin reduced the size of the protein and allowed the cells to recognize HA via CD44. This function was also induced by treatment with deglycosylating enzymes (either a mixture of endoglycosidase F and N-glycosidase F or neuraminidase alone). A possible role for glycosylation in regulation of adhesion was then sought with a series of normal and transformed murine cells. Disruption of glycosylation or treatment with deglycosylating enzymes did not induce ligand binding in an interleukin 7-dependent pre-B cell line, and splenic B cells also appeared to be in an inactive state. Some normal B cells acquired the ability to recognize HA after stimulation with lipopolysaccharide or interleukin 5 and had distinctive surface characteristics (loss of immunoglobulin D and acquisition of CD43). An additional subset of activated cells might have been in a transitional state, because the cells bound ligand after neuraminidase treatment. The ligand-binding ability of a purified CD44-immunoglobulin fusion protein dramatically increased after neuraminidase treatment. Thus, differential glycosylation of this molecule is sufficient to influence its recognition function. Cell adhesion involving HA can be regulated by multiple mechanisms, one of which involves variable glycosylation of CD44.